The influence of landscape on the spatial and temporal distribution of stream macroalgal communities of two types of subtropical biomes - Oliveira, Regis de C. [UNESP]; Tonetto, Aurelio F. [UNESP]; Peres, Cleto K.; Branco, Ciro Cesar Zanini [UNESP] (Asoc Espan Limnol-mislata, 2013)
Landscape properties must be considered in the interpretation of ecological patterns of stream macroalgal communities. In this study, we sampled streams with different types of riparian cover from two biomes (highland grassland, HG, and seasonal semideciduous forest, SSF) for a period of one year. Each stream was visited four times, once in each season, during which we observed the algal growth and recorded measurements of a set of physical and chemical properties. Nineteen macroalgal taxa were recorded for HG, while 21 were recorded for SSF, but only three species were common to both biomes. Student's t-test results showed that significant differences existed between HG and SSF only for stream depth for abiotic variables and for abundance for biotic variables, while the results of a detrended correspondence analysis (DCA) revealed that the taxonomic compositions were sharply different at the landscape level. In addition, the DCA results showed that when each landscape was considered individually, the HG macroalgal communities had a clear spatial structure, while for SSF macroalgal communities no spatial structure was detected. These results suggest that although the taxonomic richness of HG and SSF are relatively similar, the landscape conditions of each biome, mainly riparian cover types, could be relevant in the determination of quantitative and qualitative differences in the stream macroalgal communities both between and within biomes.
Keywords: Aquatic vegetation; subtropical biome; lotic systems; stream algae; South America